Blended finance and its potential for development cooperation - Karin Küblböck; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2019)
The implementation of the Agenda 2030 entails massive financing needs. The debate increasingly emphasizes the importance of the private sector and the role of aid to 'leverage' private sector investments for development. In this context, the concept of blended finance is key. This briefing paper traces the current debates about blended finance. It introduces definitions, instruments and main actors, presents existing data and provides a critical assessment of the concept.
Keywords: 330; blended finance; SDGs; European Union; development finance